2017
DOI: 10.1111/jocn.13997
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and the sense of coherence in patient–caregiver dyad versus acceptance of illness in cancer patients

Abstract: Greater support offered to caregivers may substantially strengthen the sense of coherence in caregivers and cancer patients and, therefore, may improve the functioning of patient-caregiver dyad in a situation of neoplastic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…The importance of perceived social support has been indicated in previous studies. While the stage of breast cancer did not have any relation to illness perception, functional social support was a significant factor of illness perception, which is consistent with the findings of a previous study.1 Similarly, patients with greater perceived social support and sense of coherence with caregiver showed better illness acceptance.42 With enough social support, the patients showed better treatment adherence and quality of life 43,44…”
Section: Discussionsupporting
confidence: 85%
“…The importance of perceived social support has been indicated in previous studies. While the stage of breast cancer did not have any relation to illness perception, functional social support was a significant factor of illness perception, which is consistent with the findings of a previous study.1 Similarly, patients with greater perceived social support and sense of coherence with caregiver showed better illness acceptance.42 With enough social support, the patients showed better treatment adherence and quality of life 43,44…”
Section: Discussionsupporting
confidence: 85%
“…From an empirical perspective, using a clinical sample, Langeland and Wahl (2009) have demonstrated that perceived social support can predict adults' positive development in sense of coherence. Recently, this association has been confirmed by other empirical investigations (e.g., Pasek et al, 2017). Taken together, these empirical studies indicate that the quality of social support, such as perceived autonomy support, may positively enhance undergraduate students' sense of coherence.…”
supporting
confidence: 67%
“…High PS after diagnosis may indicate that cancer diagnosis frequently lead to enhanced involvement of family members as caregivers [35]. Since the diagnosis notification affects the disease management and treatment, high PS at those times presumably help prevent recurrence fears [36] and strengthen the patients' coherence sense, an important determinant of acceptance [37]; however, during this 'diagnosis shock', both positive and negative aspects of social support seem to be intensified, as our data reveal, since the level of DI is increased in the postdiagnostic phase, especially in men. Trajectory analyses revealed a subgroup of patients with high levels and an overall increase of DI over time (group 3b), which also show higher levels of depressive symptoms compared to patients with lower and stable levels of DI.…”
Section: Course Of Ps and DImentioning
confidence: 99%